Sediment history mirrors Pleistocene aridification in the Gobi Desert (Ejina Basin, NW China) - Schwamborn, Georg Johannes; Pross, Jörg (Solid earth, 2020)
Abstract. Central Asia is a large-scale source of dust transport, but it also held a prominent changing hydrological system during the Quaternary. A 223 m long sediment core (GN200) was recovered from the Ejina Basin (synonymously Gaxun Nur Basin) in NW China to reconstruct the main modes of water availability in the area during the Quaternary. The core was drilled from the Heihe alluvial fan, one of the world's largest alluvial fans, which covers a part of the Gobi Desert. Grain-size distributions supported by endmember modelling analyses, geochemical-mineralogical compositions (based on XRF and XRD measurements), and bioindicator data (ostracods, gastropods, pollen and non-pollen palynomorphs, and n-alkanes with leaf-wax δD) are used to infer the main transport processes and related environmental changes during the Pleistocene. Magnetostratigraphy supported by radionuclide dating provides the age model. Grain-size endmembers indicate that lake, playa (sheetflood), fluvial, and aeolian dynamics are the major factors influencing sedimentation in the Ejina Basin. Core GN200 reached the pre-Quaternary quartz- and plagioclase-rich “Red Clay” formation and reworked material derived from it in the core bottom. This part is overlain by silt-dominated sediments between 217 and 110 m core depth, which represent a period of lacustrine and playa-lacustrine sedimentation that presumably formed within an endorheic basin. The upper core half between 110 and 0 m is composed of mainly silty to sandy sediments derived from the Heihe that have accumulated in a giant sediment fan until modern time. Apart from the transition from a siltier to a sandier environment with frequent switches between sediment types upcore, the clay mineral fraction is indicative of different environments. Mixed-layer clay minerals (chlorite/smectite) are increased in the basal Red Clay and reworked sediments, smectite is indicative of lacustrine-playa deposits, and increased chlorite content is characteristic of the Heihe river deposits. The sediment succession in core GN200 based on the detrital proxy interpretation demonstrates that lake-playa sedimentation in the Ejina Basin has been disrupted likely due to tectonic events in the southern part of the catchment around 1 Ma. At this time Heihe broke through from the Hexi Corridor through the Heli Shan ridge into the northern Ejina Basin. This initiated the alluvial fan progradation into the Ejina Basin. Presently the sediment bulge repels the diminishing lacustrine environment further north. In this sense, the uplift of the hinterland served as a tipping element that triggered landscape transformation in the northern Tibetan foreland (i.e. the Hexi Corridor) and further on in the adjacent northern intracontinental Ejina Basin. The onset of alluvial fan formation coincides with increased sedimentation rates on the Chinese Loess Plateau, suggesting that the Heihe alluvial fan may have served as a prominent upwind sediment source for it.